Heart and heart–liver transplantation in adults with failing Fontan physiology. Issue 8 (18th July 2018) - Reardon, Leigh C.; DePasquale, Eugene C.; Tarabay, Jana; Cruz, Daniel; Laks, Hillel; Biniwale, Reshma M.; Busuttil, Ronald W.; Kaldas, Fady M.; Saab, Sammy; Venick, Robert S.; Lin, Jeannette P.; Nsair, Ali; et al.
Abstract: Background: As the population of patients with a Fontan palliation grows so does, the number of patients with cardiac failure necessitating orthotopic heart transplant (OHT) and combined heart–liver transplant (CHLT). There is recent evidence that current era cardiac transplant in Fontan patients has improved outcomes, but most studies have a preponderance of pediatrics patients in their cohorts. We examine our institutional experience with adult OHT and CHLT transplantation for failed Fontan physiology. Methods and Results: Retrospective analysis of patients at the Ahmanson/UCLA Adult Congenital Heart Disease Center who underwent OHT or CHLT for failing Fontan physiology from January 1, 2002 to May 31, 2017. We identified 20 patients with single‐ventricle physiology and Fontan palliation who underwent OHT or CHLT. The median age was 29.5 years (range 19‐44). Five patients underwent CHLT because of biopsy proven hepatic cirrhosis. The median length of hospital stay was 23 days (range 8‐76) post‐OHT and 51 days (range 26‐77) post‐CHLT. During a median follow‐up of 56 months (range 2‐178), there was one mortality occurring at 34 months post‐OHT due to coronary vasculopathy. Most frequent early postoperative complications included bleeding and infection (55% and 20%, respectively) and surgical reintervention for bleeding complications (n = 8, 40%). One CHLT patient experienced clinically significant hepatic rejection requiring admission and steroid treatment. Conclusions: Despite inherent risks and complexities of OHT or CHLT in patients with a failed Fontan, transplant is a reasonable therapy. Peri‐ and postoperative complications are common and may require surgical reintervention. Continued observation of practices and unifying themes may help improve patient selection, pre‐ and postoperative treatment and ultimately outcomes.